Internalization of Spiritual Values in the Kanduhai Sko (Sudaih Nuwa): Traditional Ceremony in Sungai Deras Village - Sindayani, Sakini Putri; Mauliddin, Arif Iman; Patrisia, Icha Nurbahira (Institut Agama Islam Negeri Kerinci, 2022)
In the Kerinci community, especially Sungai Deras Village, Kanduhai Sko is a tradition that is considered sacred. Display various kinds and styles of worship during the Kanduhai Sko ceremony. This topic is exciting to raise because traditional ceremonies have different religious aspects. Because no community is involved in organizing this sacred ceremony, starting with children, young people, and parents who live and live in Sungai Deras Village beside this community is essential. The findings in this study dedicate religious values to the Kanduhai Sko ceremony in the Sungai Deras community. The conclusions of this study indicate spiritual values in the Kanduhai Sko ceremony for the Sungai Deras community.